Konzervipar és vidékfejlesztés - Kis, Mária (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
According to the opinion of certain specialists - who would consider themselves outstanding experts the canning industry has passed the stage of maturity and entered a declining phase of lifecycle within the industry. We, on the contrary, maintain the view, as supported by evidence in the present study, that the above position in not suitably grounded. This viewpoint may be further confirmed by considering the issue at hand through the angle of regional development and the current situation of Hungarian national economy. While refraining from giving a detailed account of the reasons underlying the world economic crisis, we would like to point out that the crisis is likely to affect economies with a well-established agriculture and, on that basis, a highly developed food industry, to a lesser degree. The situation in Hungary would have developed in a different way if we had treated the Hungarian agricultural line of business and, in particular, canning industry, as an industry of strategic importance. An attempt is made in this study to support the above view.